2013
DOI: 10.1007/s00122-013-2061-5
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and QTL mapping of Fusarium wilt race 4 resistance in cotton

Abstract: Diseases such as Fusarium wilt [Fusarium oxysporum f.sp. vasinfectum (FOV) Atk. Sny & Hans] represent expanding threats to cotton production. Integrating disease resistance into high-yielding, high-fiber quality cotton (Gossypium spp.) cultivars is one of the most important objectives in cotton breeding programs worldwide. In this study, we conducted a comprehensive analysis of gene action in cotton governing FOV race 4 resistance by combining conventional inheritance and quantitative trait loci (QTL) mapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 27 publications
5
108
1
Order By: Relevance
“…In cotton research, Ulloa et al (2013) comprehensively analyzed gene action in cotton governing Fusarium wilt (Fusarium oxysporum f sp vasinfectum, FOV) race 4 resistance by combining conventional inheritance and QTL mapping with molecular markers. They found that a single resistance gene (Fov4) had a major dominant gene action and conferred resistance to the FOV race 4 in Pima S6, which appears to be located on chromosome 14.…”
Section: Development Amplification and Characteristics Of Disease-rmentioning
confidence: 99%
“…In cotton research, Ulloa et al (2013) comprehensively analyzed gene action in cotton governing Fusarium wilt (Fusarium oxysporum f sp vasinfectum, FOV) race 4 resistance by combining conventional inheritance and QTL mapping with molecular markers. They found that a single resistance gene (Fov4) had a major dominant gene action and conferred resistance to the FOV race 4 in Pima S6, which appears to be located on chromosome 14.…”
Section: Development Amplification and Characteristics Of Disease-rmentioning
confidence: 99%
“…Understanding the underlying genetic control of biological processes for favorable traits is relevant to a range of research objectives. Such understanding has potential applications for cotton crop improvement Cao et al 2014;Lacape et al 2013;Ning et al 2014;Rong et al 2007;Ulloa et al 2005Ulloa et al , 2013.…”
Section: Introductionmentioning
confidence: 98%
“…However, due to the allopolyploid nature of the cotton genome, certain chromosomal structures remain to be resolved. These include deletions, duplications, or rearrangements that may be specific to species, or to particular crosses within or between species (Brubaker et al 1999;Guo et al 2007;Lacape et al 2009;Rong et al 2004;Ulloa et al 2013;Wang et al 2013;Yu et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-nine microsatellite markers (SSR) were analyzed from the DNA samples. The SSR analysis was performed using the same conditions described by Ulloa et al (2013). From the molecular data, it was carried out analysis by descriptive statistics and analysis by methods based on distance index and on ancestry model.…”
Section: Methodsmentioning
confidence: 99%